(untitled) (Sociologisk Forskning, 2026)
The prevalence of migration across the world poses the question inasmuch migrants will assimilate to the way of life of the receiving country? Studies of immigrants show that immigrants usually assimilate via educational attainments and economic integration. Concerning culture, however, researchers do not agree and studies show mixed results: some ethnic groups preserve to a great extent their own culture, while other immigrants assimilate into the culture of the destination country. A central cultural aspect is social trust in other persons according to many researchers. Social trust is regarded by several researchers as a central factor for democracy, wealth, and good public administration. However, although both research streams – on immigration and on trust – are well-established, there are only a limited number of studies investigating immigrants’ social trust globally. This paper examines which factors influence immigrants’ trust levels on a global scale. Immigrants’ level of trust is an important indicator of a successful integration, because it signals some form of understanding, acceptance, and feeling of comfort in the social context of the destination. The results show that the most important factor for immigrants’ trust is the destination country’s trust level. This indicates that immigrants assimilate to the destination’s way of life. Furthermore, individual factors like education, trust in public authorities, and income increase immigrants’ trust levels, but the influence of individual factors is modified by religious denomination. Overall, Muslim and Orthodox immigrants are less affected by individual factors than Protestants.